Imaging flow cytometry: from high - resolution morphological imaging to innovation in high - throughput multidimensional biomedical analysis - Huang, Qing; Zhou, Zhengyu; Lv, Qiao; Min, Qian; Jiang, Lu; Chen, Qian; Peng, Jin; Zhou, Hongli; Zhou, Ju; Dai, Qian; Zhou, Jianyun (Frontiers in Bioengineering and Biotechnology, 2025)
Imaging flow cytometry (IFC), as an extension of conventional flow cytometry, has emerged as a cutting-edge cellular analysis tool by integrating high-resolution imaging technology, and has shown significant potential and application value in biomedical research. In this paper, we comprehensively review the evolution of IFC from its early theoretical development to its current mature application, and explain its working principle, unique advantages, and the current status of its application in several biomedical fields. The paper focuses on how IFC integrates high-throughput and morphological imaging, highlighting its key role in cell biology, immunology, oncology, and environmental monitoring. Furthermore, the paper addresses the challenges and opportunities in data analysis, and proposes the potential of artificial intelligence (AI) and machine learning technologies to drive its progress. The paper concludes with an outlook on the future of IFC, predicting its application in emerging research areas and emphasizing the role of continuous technological innovation in driving the development of the field. It aims to provide researchers with a comprehensive view of IFC to promote its widespread application in biomedical research.